Toxicidade de Eugenia uniflora L. (myrtaceae) em modelos de Drosophila melanogaster e células sanguíneas humanas - Cunha, Francisco Assis Bezerra da (2015)
The increasing use of natural products has led to the imperative need of investigating the toxicological potential of secondary plant metabolites. In this context, toxicological studies were carried on Eugenia uniflora (family: Myrtaceae), a species used in Ceara state, Brazil, for medicinal purpose. Particularly, this study investigated the toxicity of E. uniflora leaf essential oil in Drosophila melanogaster as well as the toxicity of ethanolic extract of E. uniflora in human cells. The phytochemical profile of the essential oil analyzed by GC-MS and GC-FID showed curzerene (48.06%), γ-elemene (13.49%) atractilone (11.78%) and trans- β-elemenone (8.94%) as the major constituents. Polyphenolic constituents of E. uniflora ethanolic extract analysed by high performance liquid chromatography (HPLC) revealed the presence of ellagic acid (1.19%), cyanidin (0.56%), quercetin (1.58%), quercitrin (1.34%), isoquercitrin (1.01%) and Luteolin (1.01%) as the major components. The extract at the concentrations tested (1-480 μg/mL) showed no cytotoxic effect to leukocytes and erythrocytes. In addition, the extract did not have any genotoxic effect, suggesting that the extract can be consumed safely at relatively high concentrations. The extract exhibited lower DPPH radical scavenging activity in comparison to ascorbic acid, but strongly inhibited (30- 480 μg/mL) lipid Fe2+ (10 μM)-induced lipid peroxidation (LPO) in rat brain and liver homogenates The results obtained with E. uniflora leaf essential oil indicate that it induces mortality in D. melanogaster (LC50 = 5.56 μg/mL) and locomotor deficit after 12 h. Based on this observation, the flies were exposed to 3 μg/mL of essential oil for 3, 6 and 12 h. Exposure of flies to 3 h caused a significant increase in reactive species production which remained stable from 6 to 12 h. There was an increase in TBARS formation following exposure of flies to E. uniflora leaf essential oil after 6 and 12 h, and this was associated with a significant increase in GST and SOD activities. A significant increase in the expression of NQO-1 was noted after 3 h of exposure, and this was associated with a significant increase in the protein level of HSP70 after 12 h. Basal levels of Nrf2 transcription factor remained unchanged. Co-exposure of the essential oil with Paraquat (20 mM) and Fe 2+ (10 mM) increased the mortality (104.4% and 98.82%) compared to the control. Similarly, Paraquat and Fe2+ increased the locomotor deficit (35.94% and 103.1%) respectively. These results indicate the toxic effects of E. uniflora leaf essential oil on D. melanogaster and points oxidative stress as an importante mechanism of toxicity. Nevertheless, further studies should be conducted to better understand the mechanism(s) underlying its toxicity.